Diseño de un banco didáctico para realizar pruebas de energía solar fotovoltaica (2022)
Renewable energies are today one of the most economically, technologically and environmentally viable options for renewing the energy matrix. Currently in the country the need to implement this type of systems is very great. In this framework and in view of the fact that the Antonio Nariño University, Ibague, does not have a testing platform to implement these practices through laboratories, since they have been done through various applications based on Excel sheets, this desing proposal is made with its corresponding laboratory guides for testing solar photovoltaic energy in order to understand the physical phenomena that occur in them